Odpowiedź :
2x-y=10
x=5y-17
2(5y-17)-y=10
x=5y-17
10y-34-y=10
x=5y-17
10y-y=10+34
x=5y-17
9y=44 /9
x=5y-17
y=44/9
x=5*(44/9)-17
y=44/9
x=(220/9)-17
y=44/9
x=24 i 4/9 - 17
y=44/9
x=67/9
x=5y-17
2(5y-17)-y=10
x=5y-17
10y-34-y=10
x=5y-17
10y-y=10+34
x=5y-17
9y=44 /9
x=5y-17
y=44/9
x=5*(44/9)-17
y=44/9
x=(220/9)-17
y=44/9
x=24 i 4/9 - 17
y=44/9
x=67/9
2x-y=10
x=5y-17
podstawiam pod 2x
2(5y-17)-y=10
x=5y-17
9y=44
x=5y-17
y=44/9
x=5(44/9)-17
y=44/9
x=220/9-17
x=67/9
y=44/9
x=5y-17
podstawiam pod 2x
2(5y-17)-y=10
x=5y-17
9y=44
x=5y-17
y=44/9
x=5(44/9)-17
y=44/9
x=220/9-17
x=67/9
y=44/9
2x-y=10
x=5y-17
2(5y-17)-y=10
x=5y-17
10y-34-y=10
x=5y-17
10y-y=10+34
x=5y-17
9y=44 /÷9
x=5y-17
y=44/9
x=5(44/9)-17
y=44/9
x=222/9-17
y=44/9
x=67/9
x=5y-17
2(5y-17)-y=10
x=5y-17
10y-34-y=10
x=5y-17
10y-y=10+34
x=5y-17
9y=44 /÷9
x=5y-17
y=44/9
x=5(44/9)-17
y=44/9
x=222/9-17
y=44/9
x=67/9